Cutaneous tuberculosis presenting as abdominal wall cellulitis: a case report - Sandhu, Jaskirat Kaur; Kaur , Satpreet (International Journal of Contemporary Pediatrics, 2023)
Tuberculosis (TB) continues to be a prevalent disease worldwide; according to World Health Organization (WHO), children and young adolescents represent about 11% of all people with TB globally. Although TB often is cited as a disease that commonly occurs in underdeveloped countries, the evolution of drug-resistant forms of TB and infection sensitivity of immunocompromised individuals have made this disease as a focal point for developed countries as well. Although pulmonary TB is the most common form worldwide, but TB can infect any organ of the body. An uncommon version- cutaneous TB- affects <2% of all individuals with active form of TB. This case report describes a 4-month-old child who presented to us with abdominal wall cellulitis following a history of fall related injury. Incision and drainage of the pus from the fluctuant area grew acid fast bacilli on Zeihl-Neelsen staining. After the child didn’t show any improvement with intravenous antibiotics, empirical anti-tuberculosis therapy was initiated after which there was marked improvement. Cutaneous TB constitutes a very small percentage of extra-pulmonary tuberculosis and is rarely seen in paediatric age group.